Efektivitas Pembelajaran IPA Berbasis Socio-Scientific Issue Terhadap Problem Solving Skill Siswa Pada Materi Zat Aditif: (The Effectiveness of Science Learning Based on Socio-Scientific Issues on Students' Problem Solving Skills in Additives Material) - Ulfa, Ana Laili; Noor, Faiq Makhdum (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
The low problem-solving ability of students in science learning is a major problem in facing the challenges of the 21st century. This study aims to analyze the implementation of SSI-based science learning and its impact on students' problem-solving skills, as well as to assess the effectiveness of SSI-based science learning on students' problem-solving skills. The method used is a Quasi-Experimental design by applying a Pretest-Posttest Nonequivalent Group Design. Sampling techniques were conducted through random sampling, resulting in class VIII B as the experimental class and VIII A as the control class. The research instruments consisted of observation sheets and 25 multiple-choice questions that measure indicators of problem-solving skills. The results show that SSI-based science learning can be implemented very well and has a significant effect on problem-solving skills, with a significance value (2-tailed) of 0.000. In addition, SSI-based science learning also shows a fairly effective category compared to the control class, as evidenced by the results of the N-Gain test analysis reaching 65.32%. Thus, SSI-based science learning is proven to be quite effective in improving student problem solving skills on additive materials, and can be used as a contextual and relevant learning alternative in shaping students to think critically about scientific issues in the surrounding environment. Keyword: Science Learning, Socio-Scientific Issue, Problem-Solving Skill, Additives